Malaysian secondary school English teachers' attitude towards the communicative approach - Yeang, Wei Theng, 1988- author; Hanita Hassan, supervisor; Fakulti Pendidikan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Sains serta Pendidikan (Pengajaran Bahasa Inggeris sebagai Bahasa Kedua)) - Universiti Teknologi Malaysia, 2012